Analisis Biaya Tambahan (Demurrage) di Perusahaan Keagenan Kapal Akibat Penundaan Penerbitan Surat Persetujuan Berlayar (SPB) (Studi Pada PT. Adi Bahari Nuansa Banten) - Indriyani Indriyani; Retno Anggoro (SAINTARA, 2022)
This study aims to determine the occurrence of demurrage as a result of the delay in the issuance of the Sailing Approval Letter (SPB). The object of this research is a ship agency company located in Banten. This research is a qualitative research which is presented descriptively by narrating the results of observations at PT. Adi Bahari Nuansa Banten and equipped with data related to problems caused by the ship shifting process and bad weather factors that have an impact on delays in the issuance of SPB. This study shows that the ship shifting process and bad weather factors have an impact on delays in issuing SPB and cause demurrage. Collecting data on this research is done by direct observation on object research and by interview with some partipiants by random that the participants is parties involved on process of loading and unloading activiteis in PT. Adi bahari Nuansa Banten. The result oof direct observatioan oan interview get the result about both of variables on this research that is shifting and bad weather has an impact on delaying of process for issuing SPB document and the next has impact on emergence demurrage or additional cost that must be incurred by shipping company to port operator party.